2015
DOI: 10.1038/ncomms7609
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson’s-associated protein DJ-1 regulates the 20S proteasome

Abstract: The Parkinson's-associated protein, DJ-1, is a highly conserved homodimer, ubiquitously expressed in cells. Here we demonstrate that DJ-1 is a 20S proteasome regulator. We show that DJ-1 physically binds the 20S proteasome and inhibits its activity, rescuing partially unfolded proteins from degradation. Consequently, DJ-1 stabilizes the cellular levels of 20S proteasome substrates, as we show for a-synuclein and p53. Furthermore, we demonstrate that following oxidative stress, DJ-1 is involved in the Nrf2-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 71 publications
6
96
0
Order By: Relevance
“…We found that CR treatment caused a dose-dependent increase in NQO1 protein levels irrespective of sex and strain; however, the magnitude of this increase was much lower in D2 males on 40% CR (Figure 4G, Figure S3D). NQO1 also functions as a gatekeeper protein capable of competing with the 20S proteasome for interaction with different proteins (Moscovitz et al, 2015). Binding of NQO1 to the key metabolic regulator PGC-1α leads to its stabilization and protection against proteasomal degradation (Adamovich et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…We found that CR treatment caused a dose-dependent increase in NQO1 protein levels irrespective of sex and strain; however, the magnitude of this increase was much lower in D2 males on 40% CR (Figure 4G, Figure S3D). NQO1 also functions as a gatekeeper protein capable of competing with the 20S proteasome for interaction with different proteins (Moscovitz et al, 2015). Binding of NQO1 to the key metabolic regulator PGC-1α leads to its stabilization and protection against proteasomal degradation (Adamovich et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, human DJ-1 was itself recently shown to regulate the activity of the 20S proteasome (66), and presumably wild type Sdj1 functions in a similar manner in fission yeast. However, as the experiments presented here were all performed in an sdj1 ϩ wild type genetic background, and Sdj1-L169P fails to interact with Sdj1, such a function of Sdj1 is unlikely to be relevant for our analyses on the degradation of misfolded Sdj1-L169P.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many of the gene mutations that cause familial PD encode proteins involved in the UPS and/or autophagy, including PINK-1, Parkin (a ubiquitin ligase), UCH-L1 (Ub carboxy terminal hydrolase L1), DJ-1 (PARK7), and LRRK2/PRAK8 [79, 81, 82]. As with the chaperone system, choosing promising drug targets from the UPS or autophagy pathways is challenging because of the number of proteins involved (there are ~ 500 to 1000 associated just with the UPS system).…”
Section: Therapeutic Targetsmentioning
confidence: 99%